Pengembangan Media Pembelajaran Fisika Berupa Booklet pada Materi Kesetimbangan Benda Tegar - Ully Artika; Siti Anisatur Rofiqah; Effendi Effendi (Pendidikan Fisika Universitas Nurul Huda, 2022)
This study aims to develop learning media in the form of booklets and determine the eligibility level of booklets. This type of research is Research and Development (R&D) adapted by Sugiyono. The subjects of this study were students of class XI SMA Muhammadiyah 1 Belitang. The results of this research and development are learning media in the form of material booklets on rigid body equilibrium. The steps used in this research are determining potentials and problems, data collection, product design, design validation, design revision, product testing and final revision. The results of the booklet validation stage by the media expert team obtained a percentage of 80.8% and the material expert team obtained a percentage of 86.60% with very good criteria. The results of the teacher's response in the form of a questionnaire to the booklet obtained a 90% agree percentage. Whereas in the results of student responses in the form of a questionnaire to the developed booklet, the percentage results obtained were as much as the percentage of good responses as much as 63.8%. From the results of the study it can be concluded that the development of learning media in the form of booklets for class XI SMA students is feasible to use